2007
DOI: 10.3758/bf03193767
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against signal enhancement as a mechanism of direct selection by color

Abstract: Two of the possible mechanisms that have been put forward to explain precuing effects are signal enhancement and uncertainty reduction. Signal enhancement leads to processing advantages for valid information because the signal at the known input channel is enhanced, whereas uncertainty reduction allows observers to ignore confusing distractor items in a display. Both mechanisms have been reported to be involved in location precuing, but it is still unclear which of these two mechanisms is responsible for color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…It seems, then, that these components only reflect processes taking place after color selection but do not mirror the color selection process itself. Behavioral data have shown that direct selection of color only occurs when distractor items are presented (Vierck & Miller, 2007). This result suggests that advance color information enables the processing system to discriminate more easily between the target and distractor items.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…It seems, then, that these components only reflect processes taking place after color selection but do not mirror the color selection process itself. Behavioral data have shown that direct selection of color only occurs when distractor items are presented (Vierck & Miller, 2007). This result suggests that advance color information enables the processing system to discriminate more easily between the target and distractor items.…”
Section: Discussioncontrasting
confidence: 92%
“…First, behavioral studies indicate that direct selection by color only takes place when more than one item is presented. It seems that selection by color does not enhance the signal of the colored item itself, but rather allows discarding distractor items more efficiently (Vierck & Miller, 2007). Thus, it seems likely that effects of color selection might have been small or absent in this study because the displays included no distractors.…”
mentioning
confidence: 99%
“…Even though color information was not necessary for the task, valid cues resulted in better performance and invalid cues in worst performance relative to the neutral condition. Even though, on the face of it, this study appears to provide evidence for visual selection on the basis of color, recent evidence shows that color cuing in such Rapid Serial Visual Presentation experiments may have to do with uncertainty reduction rather than visual selection (see Vierck & Miller, 2007).…”
mentioning
confidence: 66%
“…The identification of targets is particularly difficult due to the low fidelity and restricted visual angle available to UAS operators, and this is made even more complicated when the target lies amidst an array of distracting information, causing uncertainty for the operators. Uncertainty describes the condition an observer experiences when viewing an image which contains confusing distracter items (Vierck and Miller, 2007). When there is a high level of uncertainty in the decision making process, humans will actively search out ways to reduce that uncertainty by gathering more information, and when all else fails, simply suppress the uncertainty and take action (Lipshitz, 1997).…”
Section: Introductionmentioning
confidence: 99%